Effects of polyaminosiloxane on the structure and properties of modified waterborne polyurethane. Issue 12 (1st November 2018) - Xu, Chengshu; OuYang, Lei; Cai, Zaisheng; Ren, Yan; Lu, Shaofeng; Shi, Wenzhao
ABSTRACT: A waterborne polyurethane (WPU) prepolymer was synthesized with poly(tetramethylene glycol) to form the soft segment, dimethylolpropionic acid as a hydrophilic chain extender, and isophorone diisocyanate. Moreover, the graft and block copolymer emulsification of WPU–polysiloxane and their films was carried out through reactions between the WPU prepolymer, aminoethyl aminopropyl dimethicone (AEAPS), and a linear polyether‐blocked amino silicone (LEPS), respectively. The properties of the structure and formed films of the WPU were characterized with Fourier transform infrared spectrometry, gel permeation chromatography, X‐ray diffraction, thermogravimetric analysis, dynamic thermomechanical analysis, and X‐ray photoelectron spectroscopy; the measurement of the water contact angle; the testing of the water absorption; and so on. The WPU–polysiloxane emulsion showed a high stability, and the molecular weight of WPU increased. Moreover, the glass‐transition temperature ( T g ) of the soft segment of polysiloxane that was incorporated into the WPU shifted to a lower temperature range, whereas the T g of the hard segment shifted to a higher temperature range, and the crystallinity of the WPU–polysiloxane film was reduced. There was a greater degree of crosslinking and accumulation of polysiloxane segments on the surface of the WPU emulsion that was modified with AEAPS in comparison to the LEPS‐modified WPU emulsion. Therefore, the water resistance of the AEAPS‐modified WPU was higher than that of the LEPS‐modified WPU. The rigidity and elasticity of the WPU–polysiloxane film improved, whereas its tensile strength did not change much after AEAPS was used. However, this was not true after LEPS was used, as the tensile strength decreased significantly. Nevertheless, the flexibility and plasticity of the WPU–polysiloxane film were enhanced after LEPS was used. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47226. Abstract :